Stereoselective allylation of α-hydroxy aldimines and its application to the formal synthesis of (−)-β-conhydrine. Issue 4 (25th January 2018) - Lee, Yong-Taek; Jung, Changyoung; Myeong, In-Soo; Lee, Sang-Hyun; Kim, Jin-Seok; Ham, Won-Hun
Abstract: Stereoselective allylation of N - p -methoxyphenyl (PMP)-substituted α-hydroxy aldimines is described. Several Lewis acids (BF3 ·OEt2, SnCl4, TiCl4, ZnCl2, and MgBr2 ·OEt2 ) were employed to mediate the allylation reactions. The addition of the allyl group generates a new stereocenter and affords the syn vicinal amino alcohol. Formal synthesis of (−)-β-conhydrine (1 ) was accomplished via syn -selective allyl addition to N -PMP-substituted α-hydroxy aldimine. Graphical abstract: